Modeling and experimental verification of the thermodynamic properties of hydrogen storage materials - Ledovskikh, A.V.; Danilov, D.L.; Vliex, M.; Notten, P.H.L. (International journal of hydrogen energy, 2016)
A new mathematical model has been developed describing the thermodynamics of the hydrogen absorption and desorption process in Metal Hydrides via the gas phase. This model is based on first principles chemical and statistical thermodynamics and takes into account structural changes occurring inside hydrogen storage materials. A general state equation has been derived considering the chemical potentials of reacting species and volume expansion, from which the equilibrium hydrogen pressure dependence on the absorbed hydrogen content can be calculated. The model is able to predict the classical Van ’t Hoff equation from first-principle analytical expressions and gives more insight into the various hydrogen storage characteristics. Pressure-Composition Isotherms have been simulated for various hydride-forming materials. Excellent agreement between simulation results and experimental data has been found in all cases. •Mathematical modeling of Pressure Composition Isotherms of Hydrogen storage materials.•Thermodynamic model experimentally verified.•Generalized form Van ′t Hoff relationship derived from first principles thermodynamics.•Palladium and intermetallic (non)-stoichiometric compounds modeled.